Language Change in Social Media - Syamsul Bahri; Elisa Betty Manullang; Putri Syah Nadillah Sihombing; Kevin Enzo Eleazar (RIRAI Publisher, 2023)
Nowadays currently, many people are found using language that sometimes runs away from the standard or changes from the standard. They use language only based on their desires. These language changes give the impression of making readers or the public may be confused to understand the true meaning. This makes researchers interested in discussing this issue. This study will focus on the exploration of language change that occurs in social media nowadays. The authors will draw inspiration from various texts on social media. The researchers will complete the survey and the study using Internet facilities. This study was conducted qualitatively and the writers will also be observing the language change directly from the relevant social media applications. The information gathered is terminological in nature, replete with human characteristics, and based on captions from several social media platforms including Twitter, Instagram, YouTube, and Facebook. Following the completion of this study, the researcher discovered that the vocabulary used by social media users to connect with one another had changed. After the researcher analyzed the data obtained, the researcher found that the semantic change was the biggest change that had been found. As much as 32% of language changes occur in social media and this illustrates that quite a lot of social media users do not use meanings that are not following their standards. Researchers also found that 10% of language changes occurred in the field of morphology. This illustrates that a few social media users result in language changes in the syntax field